Process optimization of microfluidic device batch production machine - Wongso, Ricolas (2014)
After years of development, microfluidic device are currently reaching the critical transition period between laboratory use and industrial application. Recent development also shows that plastics or polymers are gaining popularity over glass and silicon microfluidic devices because they are more affordable. Hot-embossing is considered as one of the economically viable process to mass produce polymer microfluidic devices. Based on these motivations, a new hot-embossing machine had been designed and built for batch production purpose. Preliminary experiments were done in order to find the processing windows of the process. Design of Experiment (DOE) was done in order to find the optimum process parameters to produce parts with the desired quality. As results, embossing temperature has been identified as the most significant factor to the output responses, followed by embossing force and embossing time. The proposed optimum process parameters are 92 oC, 1304 N, and 60 second respectively. Confirmation runs using these optimum settings show that the process is able to produce good quality parts and stable.